Comparison of Ralgro® and Compudose® implants for suckling steer calves - D. Simms; A. Dinkel; D. Jepsen; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1983)
Two field trials were conducted to compare Ralgro and Compudose for suckling steer calves. Ralgro, Ralgro re-implanted, and Compudose increased gain over controls 2.5. 5.9, and 1.5%, respectively, with only the increase from Ralgro re-implanted being signficicant (P<.05). Ralgro reimplanted steers gained more than Compudose steers (P<.05).
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Implants; Steers